Performance of compressed air engine modified from spark ignition engine with cam modification - Baskaran, Barathan (Universiti Sains Malaysia, 2017)
As non-renewable energy depletes as the day goes by, increasing variety pollutions all around the world creating an unbalanced atmosphere. Development of technologies to overcome this situation has been already begun. One of the innovations is to create an engine where the fuel used is compresses air. The engine used particularly for this research is the HONDA G200 4 stroke gasoline engine where it has been modified to a 2 stroke engine to increase power and efficiency. The cam lobe has been modified in order to convert 4 stoke to 2 stroke engine. As the fuel used is compressed air, overlap in valve and cam would cause power loss because a certain amount of compressed air that comes through the intake port will immediately exit through exhaust port without going through the cycle. Power loss will cause the engine to be less efficient. The aim of this project is to determine does the cam and valve have overlap and how much is the duration of the overlap. Then, a rope brake dynamometer system was used to determine the engine’s efficiency. A rope brake dynamometer, measures the output torque or the required driving torque of the engine. As for this particular project, a leather belt was used instead a cable for a lower friction coefficient. In the end, it was determined that the valve and cam has an overlap issue and suggestions are made on how to eliminate the overlap to minimal. The mechanical efficiency of the engine was in the range of 7% to 28% at a different variable used.